2015
DOI: 10.2341/14-162-l
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Resin Infiltration on Enamel Erosion Inhibition

Abstract: Resin-based materials that show promising effects for preventing the progression of erosion have been studied. This in vitro study evaluated the effects of applying resin-based materials, including resin infiltration, on previously eroded enamel subjected to erosive challenges. The influence of enamel surface etching prior to application of the material was also studied. Bovine enamel blocks were immersed in hydrochloric acid (HCl), 0.01 M (pH 2.3), for 30 seconds in order to form a softened erosion lesion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 48 publications
1
25
0
13
Order By: Relevance
“…In previous study, it was observed on sound and carious enamel that infiltrant alone presented higher loss of apatite than adhesive and adhesive + infiltrant in lactic acid for 21 days (Schmidlin et al, ). Another study found that infiltrant and resin sealant remained over the eroded enamel and offered protection even after erosive challenges (HCl for 2 min—four times/day) for 5 days (Oliveira et al, ). Despite the positive outcomes achieved for application of infiltrant and resinous sealant in dental erosion, further in vitro and in situ studies are necessary to evaluate the retention and durability of these materials in enamel and dentin before they might be applied for clinical purpose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous study, it was observed on sound and carious enamel that infiltrant alone presented higher loss of apatite than adhesive and adhesive + infiltrant in lactic acid for 21 days (Schmidlin et al, ). Another study found that infiltrant and resin sealant remained over the eroded enamel and offered protection even after erosive challenges (HCl for 2 min—four times/day) for 5 days (Oliveira et al, ). Despite the positive outcomes achieved for application of infiltrant and resinous sealant in dental erosion, further in vitro and in situ studies are necessary to evaluate the retention and durability of these materials in enamel and dentin before they might be applied for clinical purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The application of resin-based materials has been studied as an alternative for minimally invasive treatment of erosion lesions (Buzalaf et al, 2014). Resin sealants, dental bonding agents and infiltrant were able to protect the tooth against erosive challenge by forming a mechanical layer over the enamel (Azzopardi et al, 2001(Azzopardi et al, , 2004Bartlett et al, 2011;Oliveira et al, 2015;Sundaram et al, 2007;Wegehaupt et al, 2013). The penetration of resin-based materials is very important for material's durability, such as their adhesion to the dental structure and their resistance to oral degradation (Buonocore et al, 1968;Kugel and Ferrari, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluoride and alternatives to fluoride for the prevention and treatment of dental erosion has been suggested based on scientific data originated from in vitro and in situ studies [15,[21][22][23]. However there is no standardized protocol for in situ studies, additionally the influence of the area of the mouth in which the removable appliance is located and the ideal period between erosive challenges on the rehardening of eroded enamel is unknown.…”
Section: Discussionmentioning
confidence: 99%